Identification of Key Drivers and Path Transmission of Carbon Emissions from Prefabricated Buildings: Based on System Dynamics - Jing Cheng; Liping Li; Rui Zhang; Liang Tian; Yanhui Liu (Buildings)
In order to achieve the ‘dual carbon’ goal, based on the DEMATEL-ISM model, 19 main factors affecting the carbon emissions of prefabricated buildings were preliminarily identified from five dimensions, including government decision-making, technical environment, social economy, energy consumption, and market supply and demand. The logical relationship, hierarchical structure, and importance between the factors were clarified, and finally, the four influencing factors were determined. According to the causal feedback relationship between the above four factors in the system flow from 2010 to 2030, eight different control scenarios were proposed, and the impact and change trend of each control scenario on the reduction of carbon emissions of prefabricated buildings were analyzed. The research results show that the key factors for carbon emissions from prefabricated buildings include 14 outcome factors and 5 cause factors, and that the causal factors are key drivers. They are the standard specification system, the incremental cost of prefabricated buildings, investment in scientific and technological innovation, and the level of prefabricated integrated technology. The key factors were structurally stratified from the essential level to the superficial level in four tiers. The first tier of the standard specification system is the surface causal factor affecting carbon emissions from prefabricated buildings. Investment in scientific and technological innovation in the second and third tiers, and the level of prefabricated integrated technology are the causes of the transition. The incremental cost of prefabricated buildings at the fourth level is the essential causal factor. Finally, based on the data related to carbon emissions of prefabricated buildings in Yunnan, China, and verified in eight regulatory scenarios, the results of the study can effectively reveal the carbon emission reduction transmission path of prefabricated buildings, which can provide a reference for the development of prefabricated buildings and carbon emission reduction strategies.